2020
DOI: 10.1136/sextrans-2019-054360
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the impact of changing drug-use trend on HIV, hepatitis C and syphilis epidemics among people who use synthetic drug-only, polydrug and heroin-only during 2005–2035 in China: modelling study

Abstract: ObjectiveThe rapid expansion of the recreational drug market becomes a global health concern. It is worrying that the bacterial and viral infection epidemics linking to drug use may worsen accordingly. This study aimed to estimate the impacts of changing trend and behaviours of using heroin only, synthetic drug (SD) only and polydrug (using SD and heroin concurrently) on HIV, hepatitis C virus (HCV) and syphilis epidemics among people who use drugs in China by 2035.MethodsWe constructed a compartmental model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to Chinese national sentinel surveillance, the prevalence of HIV among drug users is ranged from 3.0 to 4.5%, and the HCV prevalence rate is 33.4–41.8% during 2010–2015 ( 5 ). A modeling study estimated that HIV and HCV prevalence expected to increase, respectively, from 10.9 and 61.7 to 19.0 and 69.1% among people using polydrugs (using synthetic drugs and heroin concurrently) from 2005 to 2035 ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Chinese national sentinel surveillance, the prevalence of HIV among drug users is ranged from 3.0 to 4.5%, and the HCV prevalence rate is 33.4–41.8% during 2010–2015 ( 5 ). A modeling study estimated that HIV and HCV prevalence expected to increase, respectively, from 10.9 and 61.7 to 19.0 and 69.1% among people using polydrugs (using synthetic drugs and heroin concurrently) from 2005 to 2035 ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review showed that the proportion of drug injection among heroin-only users remained at 82.2% during 2006–2015, while the ratio increased from 58.6 to 65.2% among people using polydrug during 2012–2015. The proportion of syringe sharing in people using polydrug remained stable in a range of 20–30% and decreased from 38.6 to 22.1% during 2005–2015 ( 6 ). The mean number of sexual partners in the heroin-only users and polydrug users was 1.04 and 5.3, respectively ( 6 ), 37% of male injecting drug users reported having MSP ( 10 ), and even 75.21% of methamphetamine users reported having sex with multiple partners after using drugs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heroin, MDMA, methamphetamine, and other hard narcotics are commonly cut with fentanyl to increase their potency. Chinese polydrug users who combined heroin and synthetic drugs (SD) (mostly IMF), when compared to either exclusive heroin or SD use, exhibited more frequent drug use, higher drug sharing (among friends and at gatherings), and riskier sexual behavior (76). Chinese PWID who combined heroin and SD were also more likely to have HIV (10.5%) and syphilis (3.6%) compared to single drug users.…”
Section: The Public Health Consequences Of Increased Production Of Im...mentioning
confidence: 99%